Serving the army as secretaries: intersectionality, multi-level contract and subjective experience of citizenship - Lomsky-Feder, Edna; Sasson-Levy, Orna (The British journal of sociology, 2015)
With the growing elusiveness of the state apparatus in late modernity, military service is one of the last institutions to be clearly identified with the state, its ideologies and its policies. Therefore, negotiations between the military and its recruits produce acting subjects of citizenship with long‐lasting consequences. Arguing that these negotiations are regulated by multi‐level (civic, group, and individual) contracts, we explore the various meanings that these contracts obtain at the intersectionality of gender, class, and ethnicity; and examine how they shape the subjective experience of soldierhood and citizenship. More particularly, we analyse the meaning of military service in the retrospective life stories of Israeli Jewish women from various ethno‐class backgrounds who served as army secretaries – a low‐status, feminine gender‐typed occupation within a hyper‐masculine organization. Findings reveal that for women of the lower class, the organizing cultural schema of the multi‐level contract is that of achieving respectability through military service, which means being included in the national collective. Conversely, for middle‐class women, it is the sense of entitlement that shapes their contract with the military, which they expect to signify and maintain their privileged status. Thus, while for the lower class, the multi‐level contract is about inclusion within the boundaries of the national collective, for the dominant groups, this contract is about reproducing social class hierarchies within national boundaries.